2008
DOI: 10.1007/s11595-007-4513-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of material surface structure similar to hydrophobic structure of lotus leaf

Abstract: Nano/micro replication, a technique widely applied in the microelectronics field, was introduced to prepare the hydrophobic bionics microstructure on material surface. Poly(vinyl alcohol) (PVA) and polystyrene (PS) moulds of the mastoid microstructure on lotus leaf surface were prepared respectively by the nano/micro replication technology. And poly(dimethylsiloxane) (PDMS) replicas with the mastoid-like microstructure were prepared from these two kinds of polymer moulds. Scanning electronic microscope (SEM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Since the last decade, many reports on the development of lotus leaf-like surface morphology using the lotus leaf itself as a biological template are available [73,74,75,76,77,78,79,80,81,82,83,84]. Seven years after Barthlott and Neinhuis’s investigation on the surface micro/nanostructure of the lotus leaf, Ji’s research group reported for the first time the development of a superhydrophobic artificial lotus leaf surface using the original lotus leaf as a natural template [73].…”
Section: Development Of Lotus Leaf-like Surface Morphology To Achimentioning
confidence: 99%
“…Since the last decade, many reports on the development of lotus leaf-like surface morphology using the lotus leaf itself as a biological template are available [73,74,75,76,77,78,79,80,81,82,83,84]. Seven years after Barthlott and Neinhuis’s investigation on the surface micro/nanostructure of the lotus leaf, Ji’s research group reported for the first time the development of a superhydrophobic artificial lotus leaf surface using the original lotus leaf as a natural template [73].…”
Section: Development Of Lotus Leaf-like Surface Morphology To Achimentioning
confidence: 99%
“…In addition, nanopillars with aspect ratios of 2 and 5 with different spacings were shown to affect the contact angle [36]. It was also shown that superhydrophobicity can be obtained using flower-like sub-microsphere roughness, but also by micropillar arrays and micropyramid structures, when a hydrophobic nanostructure was added on top of the microstructures [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 98%
“…A smearing of Raman modes upon the order-disorder transition from pyrochlore to defect fluorite structure was also observed for Gd 2 Zr 2 O 7 and ascribed to the presence of microdomains [27]. Although the generalized nature of the density of phonon states derived from INS impedes its usage for the calculation of thermodynamic quantities, the GDOS of pyrochlore and defect fluorite Nd 2 Zr 2 O 7 can still be used to calculate the difference of the respective generalized vibrational entropies, i.e., S vib = S vib (P) − S vib (DF), which results in S vib = 2.43(5) k b /atom−2.14(5) k b /atom = 0.29 (7) k b /atom at room temperature 2 . Assuming that the densities of phonon states do not significantly change with temperature, the vibrational 1 The GDOS g(E) can be approximated by g(E) = A −1 Σ i N i b 2 c,i g i (E)/ M i , where A is a normalization constant, g i (E) is the DPS specific to element i, N i is their relative number, M i is the atomic mass and b i is the neutron scattering length.…”
Section: Papermentioning
confidence: 99%
“…Further interest in zirconates adopting the pyrochlore structure is stimulated by their resistance against amorphization upon (self-)irradiation due to an order-disorder transition from pyrochlore to defect fluorite, which renders them promising candidates for nuclear waste management [5]. Moreover, due to their very low thermal conductivity pyrochlore-based materials may find applications in the area of thermal barrier coatings [6][7][8].…”
Section: Introductionmentioning
confidence: 99%